Toward a Multilevel Extension and Cross-Cultural Assessment of the 2 x 2 Model of Perfectionism - Franche, Véronique (Université d'Ottawa / University of Ottawa, 2017)
Perfectionistic standards are ubiquitous features conveyed in several aspects of life. Although some aspects of perfectionism may be beneficial to promote achievement, continuously targeting perfection and flawlessness has been shown to impede on one’s psychological adjustment, motivation, and self-regulation (Hewitt & Flett, 1991). Essentially, there still exists no consensus among researchers to identify whether perfectionism—or at least, some facets of perfectionism— is likely to promote or undermine positive outcomes (e.g., Gotwals, Stoeber, Dunn, & Stoll, 2012). The 2 × 2 model of perfectionism (Gaudreau, 2012; Gaudreau & Thompson, 2010) is a welcome addition for researchers studying perfectionism because it proposes an open-ended theoretical system in which novel hypotheses are amenable to empirical scrutiny, thus offering leeway for researchers to theorize and reinterpret those past mixed findings. The overarching goal of this dissertation was to address some of the gaps of the perfectionism literature in order to better understand under which circumstances perfectionistic standards are useful to foster achievement without thwarting psychological adjustment. Accordingly, the current dissertation used the 2 × 2 model of perfectionism as theoretical framework to propose four original studies regrouped under three articles. In Article 1, we aimed at providing a multilevel extension of the 2 × 2 model in order to better understand how the relationships between subtypes of perfectionism and indicators of positive and negative psychological adjustment may vary according to the level of analysis that is being studied. In other words, in this study, we examined the within-person relationships between subtypes of perfectionism and psychological adjustment (i.e., accounting for the fact that these relationships may vary within each person from one life domain to another) in complement to the between-person relationships (i.e., accounting for individual differences across people). A sample of 338 undergraduate students completed measures of perfectionism, vitality, goal progress, affect, and stress for each life domain in which they reported being invested. Preliminary analyses of multilevel confirmatory factor analysis supported the multilevel factorial structure of our measure. Furthermore, results of multilevel regressions with random coefficient supported most hypotheses of the model with positively-, but not negatively-worded outcomes, deserving further discussion. In an attempt to better understand these unexpected yet interesting findings, Article 2 aimed at extending the findings of Article 1 by examining the multilevel associations between subtypes of perfectionism and coping strategies of undergraduate students. Two studies were conducted to examine the between- and within-person relationships respectively. Accordingly, 332 undergraduate students completed measures to assess their dispositional perfectionism and coping tendencies in Study 1 (i.e., between-person). In Study 2, 203 undergraduate students completed repeated measures of perfectionism and coping for each life domain in which they reported being invested (i.e., within-person). Results of multiple regressions from Study 1 (i.e., between-person) showed similar findings than those obtained in past research with task- and disengagement-oriented coping, and support of all four hypotheses was obtained with relative coping (i.e., proportion of task-oriented compared to one’s overall coping). Results of multilevel regressions with random coefficient from Study 2 (i.e., within-person) provided support for all hypotheses with disengagement-oriented coping, two hypotheses with task-oriented coping, and three hypotheses with relative coping. Finally, in Article 3, we aimed at identifying the potential role of moderators in the 2 × 2 model of perfectionism, particularly the role of sociocultural identity. A sample of 697 undergraduate students (538 Euro Canadians and 159 Asian Canadians) completed measures aimed at assessing perfectionism and indicators of school achievement (i.e., satisfaction and grade-point average). Preliminary multi-group confirmatory factor analyses with invariance testing supported the factorial structure of our measure across both samples, thus rendering the measure equivalent across both sociocultural groups. Furthermore, results provided support for our socially prescribed perfectionism as a cultural makeup hypothesis, suggesting that Asian Canadians with a subtype of mixed perfectionism (i.e., high self-oriented and high socially prescribed perfectionism)—in contrast to their Euro Canadians counterparts—were able to reach both the achievement and satisfaction targets known to play an important part in the positive academic experience of students. Overall, the current dissertation bears significant theoretical implications by providing further validation of the 2 × 2 model of perfectionism, as well as supporting a multilevel and cross-cultural extension. It also holds methodological contributions by supporting the factorial invariance of the short-Multidimensional Perfectionism Scale across levels of analysis and sociocultural groups. Furthermore, this dissertation involves practical implications for clinical psychologists by underlining the need to compare clients to their own average across significant domains of their life (e.g., to monitor their progress or areas of concern) along to the normative standards designed to compare them with individuals (e.g., to monitor their levels in comparison to the population).
Keywords: Perfectionism; Coping; Academic adjustment; Multilevel modeling; Cross-cultural